Degradation process of lead chromate in paintings by Vincent van Gogh studied by means of synchrotron X-ray spectromicroscopy and related methods. 2. Original paint layer samples - Monico, Letizia; Van der Snickt, Geert; Janssens, Koen; De Nolf, Wout; Miliani, Costanza; Dik, Joris; Radepont, Marie; Hendriks, Ella; Geldof, Muriel; Cotte, Marine (Analytical chemistry (Washington), 2011)
The darkening of the original yellow areas painted with the chrome yellow pigment (PbCrO(4), PbCrO(4)·xPbSO(4), or PbCrO(4)·xPbO) is a phenomenon widely observed on several paintings by Vincent van Gogh, such as the famous different versions of Sunflowers. During our previous investigations on artificially aged model samples of lead chromate, we established for the first time that darkening of chrome yellow is caused by reduction of PbCrO(4) to Cr(2)O(3)·2H(2)O (viridian green), likely accompanied by the presence of another Cr(III) compound, such as either Cr(2)(SO(4))(3)·H(2)O or (CH(3)CO(2))(7)Cr(3)(OH)(2) [chromium(III) acetate hydroxide]. In the second part of this work, in order to demonstrate that this reduction phenomenon effectively takes place in real paintings, we study original paint samples from two paintings of V. van Gogh. As with the model samples, in view of the thin superficial alteration layers that are present, high lateral resolution spectroscopic methods that make use of synchrotron radiation (SR), such as microscopic X-ray absorption near edge (μ-XANES) and X-ray fluorescence spectrometry (μ-XRF) were employed. Additionally, μ-Raman and mid-FTIR analyses were carried out to completely characterize the samples. On both paint microsamples, the local presence of reduced Cr was demonstrated by means of μ-XANES point measurements. The presence of Cr(III) was revealed in specific areas, in some cases correlated to the presence of Ba(sulfate) and/or to that of aluminum silicate compounds.